2013
DOI: 10.5812/nephropathol.10113
|View full text |Cite
|
Sign up to set email alerts
|

Candiduria in children and susceptibility patterns of recovered Candida species to antifungal drugs in Ahvaz

Abstract: Background: Candiduria presents as an increasingly common nosocomial infection, which may involves urinary tract. Spectrum of disease is varying from asymptomatic candiduria to clinical sepsis. Disease is most commonly caused by Candida albicans. Objectives: The aim of the present study was to determine the frequency of candiduria in children attending Abuzar Pediatrics Hospital. Patients and Methods: Urine samples were collected from 402 patients attending to the Abuzar Pediatrics Hospital, Ahvaz. 10µl of eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
10
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 22 publications
6
10
1
Order By: Relevance
“…In the present study, males (63%) were more commonly affected than females (37%) and candiduria was most common in infants (44%). This result is comparable with other study conducted by Seifi Z et al [10] where 71.4% of candida was isolated in males and 28.6% in females [10].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, males (63%) were more commonly affected than females (37%) and candiduria was most common in infants (44%). This result is comparable with other study conducted by Seifi Z et al [10] where 71.4% of candida was isolated in males and 28.6% in females [10].…”
Section: Discussionsupporting
confidence: 91%
“…However, 17.64% of diabetic patients had infection which could be due to their increased tissue glucose level, facilitating the growth of Candida. Our finding is close to that reported by Seifi et al (2013) who found an infection rate of 14.3% in children in Ahvaz.…”
Section: Discussionsupporting
confidence: 79%
“…Several reports indicated that nosocomial UTIs frequently encountered in patients admitted to ICUs (1,6,8,9,11,12). The incidence of candiduria has significantly increased among ICU patients, especially in those with indwelling urinary catheters (1).…”
Section: Discussionmentioning
confidence: 99%
“…The high incidence of funguria in Iranian ICU patients should be considered as very critical (9)(10)(11)(12). According to (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation